2021
DOI: 10.7181/acfs.2021.00017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-2019 on plastic surgery emergencies in Korea

Abstract: Since the first case of an epidemic viral pneumonia in Wuhan, China in December 2019, the infection rapidly spread. The causative virus was a novel coronavirus and was named corona-virus disease 2019 (COVID-19) [1,2]. With a high infectivity, COVID-19 spread worldwide, and as a response, the World Health Organization after all declared the infection a global pandemic on March 11, 2020 [3]. In South Korea, the number of confirmed cases of COVID-19 has risen progressively since the first confirmed case in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A total of five articles noted an increase in unintentional injuries overall ( 74–78 ) when comparing the lockdown period to the same time period in previous years, though none were significant. One research team in South Korea noted they observed a significant decrease in unintentional injuries resulting in facial trauma, but increases in hand trauma when compared to the same period in 2019 ( 59 ). Lastly, two studies indicated no differences in unintentional injuries during the pandemic period compared to pre-pandemic periods ( 79 , 80 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of five articles noted an increase in unintentional injuries overall ( 74–78 ) when comparing the lockdown period to the same time period in previous years, though none were significant. One research team in South Korea noted they observed a significant decrease in unintentional injuries resulting in facial trauma, but increases in hand trauma when compared to the same period in 2019 ( 59 ). Lastly, two studies indicated no differences in unintentional injuries during the pandemic period compared to pre-pandemic periods ( 79 , 80 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have indicated an increased rate of lacerations in trauma patients during the pandemic [ 16 ]. Similarly, our results demonstrated a surge in the ED presentations with genitourinary laceration as the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In plastic surgery, skin grafting is a good reconstructive option to cover skin defects caused by head and neck cancers or trauma. The decrease in outdoor activity due to the COVID-19 pandemic has reduced the rate of facial trauma, but the incidence of facial skin cancer is steadily increasing [ 7 , 8 ]. Common donor sites of full-thickness skin grafts (FTSGs) for head and neck reconstruction are the preauricular skin, retroauricular skin, the clavicle, and inner upper-arm regions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%